Analysis of serum antioxidant capacity and gut microbiota in calves at different growth stages in Tibet - Zhang, Xinyu; Cao, Zhijun; Yang, Hongjian; Wang, Yajing; Wang, Wei; Li, Shengli (Frontiers in Microbiology, 2023)
The hypoxic environment at high altitudes poses a major physiological challenge to animals, especially young animals, as it disturbs the redox state and induces intestinal dysbiosis. Information about its effects on Holstein calves is limited. Here, serum biochemical indices and next-generation sequencing were used to explore serum antioxidant capacity, fecal fermentation performance, and fecal microbiota in Holstein calves aged 1, 2, 3, 4, 5, and 6 months in Tibet. Serum antioxidant capacity changed with age, with the catalase and malondialdehyde levels significantly decreasing (P < 0.05), and superoxide dismutase levels significantly increasing (P < 0.05) with age. No significant differences (P > 0.05) in total volatile fatty acid levels were noted between the groups. In all groups, Firmicutes, Bacteroidetes, and Actinobacteria were the three most dominant phyla in the gut. Gut microbial alpha diversity significantly increased (P < 0.05) with age. Principal coordinate analysis plot based on Bray–Curtis dissimilarity revealed significant differences (P = 0.001) among the groups. Furthermore, the relative abundance of various genera changed dynamically with age, and the serum antioxidant capacity was associated with certain gut bacteria. The study provides novel insights for feeding Holstein calves in high-altitude regions.